EVALUATION EVALUATION OF THE QURAN TEACHER TRAINING PROGRAM AT SDIT ANAK SHALIH BOGOR ISLAMIC SCHOOL USING THE UMMI METHODE - Fatonah, Umi; Erawati saragih, Enni; Maimunah; Safitri, Ani; Ridho, Iqromi (Program Studi Teknologi Pendidikan FKIP Universitas Ibn Khaldun, Bogor, 2026)
This research is an evaluation study using the Kirkpatrick model. It aims to provide an in-depth overview of the implementation and outcomes of a training program conducted using the UMMI method to improve the quality of Quranic teaching for teachers and also to improve future education. The research method was qualitative, using data collection instruments such as interviews, observations, questionnaires, and documentation. The results showed a very high level of participant satisfaction with the training, indicating that the implementation was effective and met their expectations. Furthermore, participants' attitudes also experienced positive changes, becoming more disciplined and meticulous in their teaching process, which is expected to improve the quality of classroom learning. The majority of participants felt a significant change in their teaching methods, with more structured and effective methods resulting in a higher quality learning process. This indicates that the training contributed significantly to improving the quality of classroom learning processes and outcomes.